Analisis Pemborosan Sistem Produksi Ban Vulkanisir Menggunakan Metode Lean Six Sigma - Hero Rinto Staenari; Hidayat Hidayat; Yanuar Pandu Negoro (Universitas Islam Raden Rahmat, Malang, 2024)
CV. Citra Buana Mandiri is a used tire recycling or retreading industry, in one month the company is able to produce 800 retreaded tires. The company's production line indicates the occurrence of waste, where one of the concerns is the level of defects produced. The purpose of this research is to identify and minimize waste to improve efficiency in the production line. The method used in this research will be an integration between Lean and Six Sigma. The results of this study show that defects and motion dominate the waste that occurs with a score of 3.60 and 3.0. In addition, the sigma level in the company's production process is at a fairly good level with a value of 3.29. Thus, the suggestions that can be given are related to the evaluation and supervision of SOP implementation and process improvement as well as material and finished product storage.